Effect of postdilatation following balloon expandable transcatheter aortic valve implantation. Issue 6 (27th December 2019) - Kawaguchi, Tomohiro; Yamaji, Kyohei; Ishizu, Kenichi; Morinaga, Takashi; Hayashi, Masaomi; Isotani, Akihiro; Kakumoto, Shinichi; Arai, Yoshio; Sakaguchi, Genichi; Shirai, Shinichi; Ando, Kenji
Abstract: Background: Postdilatation after transcatheter heart valve (THV) implantation was associated with larger aortic valve areas in large‐scale registries; however, the specific effects of postdilatation are poorly understood. Methods and Results: Among a total of 224 consecutive patients who underwent transcatheter aortic valve replacement using SAPIEN 3, 121 patients (54.0%) underwent postdilatation (same contrast volume: N = 101, +1 ml: N = 17, +2 ml: N = 3). THV diameter was assessed (a) during, (b) after implantation, (c) during postdilatation, and (d) after postdilatation by quantitative fluoroscopy. In the overall patients ( N = 224), acute recoil was observed from during implantation (23.0 ± 2.0 mm) to after implantation (22.5 ± 2.0 mm, p  < .001) with an absolute recoil of 0.52 ± 0.25 mm. After postdilatation ( N = 121), THV diameter significantly increased from 22.5 ± 2.0 mm to 22.9 ± 2.1 mm ( p  < .001), with smaller absolute recoil (0.39 ± 0.21 mm, p  < .001). Compared with those who did not undergo postdilatation, patients who underwent postdilatation had larger postprocedural THV area assessed by multi‐slice computed tomography (471.4 ± 78.1 mm 2 vs. 447.5 ± 76.3 mm 2, p = .02) and larger effective orifice area (EOA) assessed by echocardiography throughout 1 year (at 30 day, 1.66 ± 0.33 cm 2 vs. 1.45 ± 0.27 cm 2, p  < .001; at 6 month, 1.66 ± 0.33 cm 2 vs. 1.44 ± 0.29 cm 2, p  < .001; at 1 year, 1.69 ± 0.38 cm 2 vs. 1.47 ± 0.30 cm 2, p  < .001). Conclusions: Postdilatation after implantation of the SAPIEN 3 valve produced a larger THV diameter with less acute recoil, followed by larger EOA throughout 1 year. Further studies are needed to evaluate the impact of postdilatation on long‐term clinical outcomes.